2018
DOI: 10.1186/s40168-018-0453-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods used to unveil the genetic and metabolic pool in the built environment

Abstract: BackgroundA majority of indoor residential microbes originate from humans, pets, and outdoor air and are not adapted to the built environment (BE). Consequently, a large portion of the microbes identified by DNA-based methods are either dead or metabolically inactive. Although many exceptions have been noted, the ribosomal RNA fraction of the sample is more likely to represent either viable or metabolically active cells. We examined methodological variations in sample processing using a defined, mock BE microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 78 publications
3
26
0
Order By: Relevance
“…Microorganisms can be found in every environment, including built environments-our habitat of buildings, roads, vehicles, and other human-associated spaces-and even in ultra-clean rooms and space stations [28]. Collectively, these factors mold the built environment's microbiome [29][30][31]-all the genetic material of the microbial members present, from which can be derived taxonomic identification and metabolic potential, including activities like nutrient utilization and antimicrobial production [30,32]. The indoor microbial community is a blend of microorganisms sourced from various ecosystems which seed each particular built environment.…”
Section: From Fear To Reluctant Acceptance Of the Microbial Worldmentioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms can be found in every environment, including built environments-our habitat of buildings, roads, vehicles, and other human-associated spaces-and even in ultra-clean rooms and space stations [28]. Collectively, these factors mold the built environment's microbiome [29][30][31]-all the genetic material of the microbial members present, from which can be derived taxonomic identification and metabolic potential, including activities like nutrient utilization and antimicrobial production [30,32]. The indoor microbial community is a blend of microorganisms sourced from various ecosystems which seed each particular built environment.…”
Section: From Fear To Reluctant Acceptance Of the Microbial Worldmentioning
confidence: 99%
“…An important feature to assess in any microbial community is the determination of which species present are alive and metabolically active [235]; rDNA and rRNA extracted from the same sources resulted in significantly different overall characterization of the microbiota [32,236]. Analyzing both RNA and DNA in combination, even just rRNA and rDNA, can provide further insight than just one method alone, such as the effect of environmental conditions on which microorganisms thrive while others struggle or perish.…”
Section: Built Environment Research Now and In The Futurementioning
confidence: 99%
“…The ratio between transcribed and genomic 16S rRNA sequences (rRNA/rDNA ratio) is a means of normalizing rRNA transcription against cell count, and it has been used to compare metabolic activity between populations (15, 16). The rRNA/rDNA ratio has been used to study the active microbial communities in aquatic (1720), ice sheet (21), air (22, 23), soil (2427), and activated-sludge (28, 29) environments, but it has not yet been widely applied in anaerobic digesters (30). Furthermore, as microbial ribosomal amplification is highly variable across both taxonomy and ecological strategy, the rRNA/rDNA ratio may not always be sufficient to discriminate between microbes in different metabolic states (10), and it may be particularly prone to error in populations with a mixture of amplification levels (31).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the need for the identification of microorganisms is described in pharmacopoeias such as Japanese Pharmacopoeia, European Pharmacopoeia, and United States Pharmacopoeia. The microorganisms isolated in this study were reported to live in the GE [ 26 28 ]. However, there were multiple candidate species from BLAST, and they had still not been identified as one species.…”
Section: Discussionmentioning
confidence: 99%